Pomiar i ocena działań w strumieniu wartości - Bednarz, Leszek (Performance measurement and evaluation in value stream, 2007)
Traditional performance measurement Systems hinder the implementation lean production. The paper is an attempt to identificate causes for this State. The author proposes some changes in performance measurement and evaluation value stream in lean production environment. The paper focuses on three question: How to design overall structure value stream measurement performance system?What and how to measure at different level of management? How to execute performance evaluation and feed back process control?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 325-337